The characterization of genome sequences diversity of Pseudomonas aeruginosa strains from international reference panel using wide range of in silico techniques - Petruńko, Leon; Musiał, Klaudia; Gmiter, Dawid (Acta Universitatis Lodziensis. Folia Biologica et Oecologica, 2024)
Pseudomonas aeruginosa is an important pathogen in patients suffering from Cystic Fibrosis as well as acute opportunistic infections in people without it. For the reason of P. aeruginosa having a broad range of habitats it’s diversity and adaptability lead it to be a very diverse species. Previous attempts of classifying P. aeruginosa strains based on their biochemical and genetic characteristics were made. In presented studied we performed additional characteristic of P. aeruginosa panel strains genomes using wide range of in silico approaches, including Single Nucleotide Polymorphisms (SNPs) - based phylogeny, as well as pan-genome and Intergenic Regions (IGRs) investigation. We shed light on strains diversity, expanding our knowledge about the strains assembled in this international panel. The results of our study may become the basis for further research aimed at fully understanding the pathogenesis of P. aeruginosa.